ROLE OF INNOVATION ON THE PERFORMANCE OF INDIAN BANKING SECTOR - Deepa Chauhan (PalArch's Journal of Archaeology of Egypt / Egyptology, 2022)
The Indian financial system has grown tremendously since the turn of the century. The emergence of private and international banks boosted banking innovation, resulting in the activation of technical sophistication in every banking transaction. Technology innovation allows banks to deliver greater customer service while also causing a fundamental shift in how they operate. Information technology (IT) has made inroads in almost every industry, and banking is no exception. Innovation is the keyword in the Indian banking business, and technology breakthroughs are opening new doors to success. The fire of innovation has been fueled by core banking. Customer satisfaction in the Indian banking industry has improved because of the results. The purpose of this study is to see how new technology affects customer satisfaction in the Indian banking sector.